2021
DOI: 10.3390/molecules26082108
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value and Preventive Role of Nigella sativa L. and Its Main Component Thymoquinone in Cancer: An Evidenced-Based Review of Preclinical and Clinical Studies

Abstract: In recent times, scientific attention has been paid to different foods and their bioactive components for the ability to inhibit the onset and progress of different types of cancer. Nigella sativa extract, powder and seed oil and its main components, thymoquinone and α-hederin, have showed potent anticancer and chemosensitizing effects against various types of cancer, such as liver, colon, breast, renal, cervical, lung, ovarian, pancreatic, prostate and skin tumors, through the modulation of various molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 118 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…Aging can cause prostate enlargement and become a reason of urine incontinency among old age males. Black seed oil can treat prostatitis and provide relief from this condition [ 174 ].…”
Section: Health Benefits Of Nigella Sativamentioning
confidence: 99%
“…Aging can cause prostate enlargement and become a reason of urine incontinency among old age males. Black seed oil can treat prostatitis and provide relief from this condition [ 174 ].…”
Section: Health Benefits Of Nigella Sativamentioning
confidence: 99%
“…in South Asian, Arab, African, and Mediterranean countries [13,14]. As evident from various studies, TQ has been reported to be a remarkable therapeutic agent affecting multiple molecular pathways that regulate cellular proliferation, apoptosis, and metastasis [12,15,16]. However, irrespective of its wide therapeutic efficacy, the clinical application of TQ is limited due to its poor solubility in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…22 , 23 Evidently, TQ has been shown its potential in the treatment of various types of cancer through the activation of multiple signalling pathways that lead to the apoptosis. 21 , 24 , 25 However, regardless of high potential, the major drawback of TQ is the low solubility in the aqueous solutions, which limits its uses in the clinical application. Thus, the preparation of suitable formulations of TQ can overcome this limitation to utilize its efficacy against several pathological conditions.…”
Section: Introductionmentioning
confidence: 99%